Asymmetric synthesis of H1 receptor antagonist (R,R)-clemastine - Lee, Sun Young; Jung, Jung Wha; Kim, Tae-Hyun; Kim, Hee-Doo (Archives of pharmacal research, 2015)
The first asymmetric synthesis of ( R , R )-clemastine ( 1 ) has been accomplished by the coupling of ( R )-tertiary alcohol 2 and ( R )-chloroethylpyrrolidine 3 via O -alkylation. ( R )-Tertiary alcohol 2 was synthesized by stereoselective alkylation of chiral α-benzyloxy ketone with Grignard reagent via chelation-controlled 1,4-asymmetric induction. In the reaction, chiral benzyl group acts as a chiral auxiliary as well as a protecting group. ( R )-Chloroethylpyrrolidine 3 was prepared by asymmetric transformation starting with l -homoserine lactone, in which racemization-minimized N -allylation and ring-closing metathesis were involved as key steps.